INNOVATION OF PUBLIC SERVICES BASED ON DIGITAL INFORMATION TECHNOLOGY AT THE MINISTRY OF RELIGIOUS AFFAIRS OFFICE OF DELI SERDANG REGENCY - sibuea, nunti (Jurnal Manajemen Dan Akuntansi Medan, 2025)
The problem of long control spans and having to use deep sea transportation accessing services is one of the problems in the service delivery process Public services at the Ministry of Religion Office of Deli Serdang Regency located in Tanjung Balai Deli Serdang . Development of Public Service Innovations based on Digital Information Technology at the Office The Ministry of Religion of Deli Serdang Regency is carried out as a form of implementation of the Integrity Zone (ZI) with the aim of improving the quality of public service delivery, especially considering The location of the Deli Serdang Regency area consists of sub-districts separated by ocean. The aim of this research is to determine the forms of innovation development Public Services Based on Digital Information Technology at the Ministry of Religious Affairs Office in Deli Serdang Regency . This study uses a literature study method for related literature. with the research problem. The research results show that the forms of Service Innovation Digital Information Technology-based Public Services at the Ministry of Religion Office of Deli Serdang Regency are PTSP Zuriah Smart Online, Hajj Database System, Letter Management Information System, E-Performance Employees, Information System Cooperation between the Ministry of Religion of Deli Serdang Regency and the Population and Civil Registration Office Deli Serdang Regency (SIKECAP), Integrated Data Information System (SI DATIN), TTE (Signature) Electronic), and Public Complaint Application (Whistleblowing System Application).